2023
DOI: 10.3390/cells12030424
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Chloride Affects Band 3 Protein-Mediated Anionic Transport in Red Blood Cells: Role of Oxidative Stress and Protective Effect of Olive Oil Polyphenols

Abstract: Mercury is a toxic heavy metal widely dispersed in the natural environment. Mercury exposure induces an increase in oxidative stress in red blood cells (RBCs) through the production of reactive species and alteration of the endogenous antioxidant defense system. Recently, among various natural antioxidants, the polyphenols from extra-virgin olive oil (EVOO), an important element of the Mediterranean diet, have generated growing interest. Here, we examined the potential protective effects of hydroxytyrosol (HT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The strong protective activity of HT is also displayed against heavy metal-caused damage. More specifically, HT prevented mercury-induced oxidative stress at red blood cells (RBCs) [ 24 ], as well as protecting the rat brain from arsenic (As)-induced oxidative stress [ 25 ]. HΤ is generally recognized as safe (GRAS) by the European Food Safety Authority (EFSA) and the Food and Drug Administration (FDA) and is asserted to improve human health when consumed at a minimum dose of 5 mg per day, as described in EU Regulation 432/2012 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strong protective activity of HT is also displayed against heavy metal-caused damage. More specifically, HT prevented mercury-induced oxidative stress at red blood cells (RBCs) [ 24 ], as well as protecting the rat brain from arsenic (As)-induced oxidative stress [ 25 ]. HΤ is generally recognized as safe (GRAS) by the European Food Safety Authority (EFSA) and the Food and Drug Administration (FDA) and is asserted to improve human health when consumed at a minimum dose of 5 mg per day, as described in EU Regulation 432/2012 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…HT has been shown to prevent cytokine formation, nitric oxide (NO) generation, tumor necrosis factor-alpha (TNF-α) secretion, and mRNA expression and to inhibit the expression of nitric oxide synthase (iNOS) and cyclooxygenase (COX-2). Some research has shown that HT treatment prevents acanthocyte formation observed after HgCl 2 exposure and prevents HgCl 2 induced oxidative stress damage, including ROS production, lipid peroxidation, and oxidation of the sulfhydryl group of total proteins in the plasma membrane [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…To fulfill their tasks, RBCs are capable of elastically deforming during mechanical stress and pass via the narrow microcirculation capillaries [ 19 , 20 ]. There is compelling evidence that treatment of RBCs with oxidizing compounds not only impair their deformability but also change their shape, thus suggesting a key role of intracellular redox status, both in structural characteristics and the control of deformability [ 21 , 22 , 23 , 24 , 25 , 26 ]. Surprisingly, a close relationship between oxidative stress and RBC deformability has also been reported in experimental investigations involving patients with sickle cell disease.…”
Section: Introductionmentioning
confidence: 99%